A Highly Miniaturized and Inherently Conjugately Matched Folded Dipole-Based RFID Tag Antenna - Sanghamitro Das; Hossein Saghlatoon; Pedram Mousavi; Ashwin K. Iyer (IEEE Access, 2019)
A novel miniaturized printed folded dipole antenna has been designed and its usefulness as an RFID tag has been demonstrated. It has been shown that the input impedance of the antenna can be engineered to achieve the required complex impedance by employing series-LC loading and unequal arm widths. The end result is a conjugately well-matched 75%-miniaturized folded dipole antenna that does not require an external matching network and exhibits a useful 30.93% radiation efficiency and 8.09 m simulated read range. Experimental validation of a fabricated prototype demonstrates excellent agreement with simulations.